STUDI KARAKTERISTIK SUB DAERAH ALIRAN SUNGAI DEDAI PADA DAERAH ALIRAN SUNGAI MELAWI KABUPATEN SINTANG - Alpius Alpius; Riduansyah Riduansyah; Asadi Asadi (Fakultas Pertanian Universitas Tanjungpura, 2022)
Dedai Sub watershed condition at this time has many changes of form and fuction caused by the opening of land activities, illegal gold mining and household garbage. This research aims to study the characteristic and profile of each characteristic Dedai Sub Watershed. In this study, only limited to the characteristic of the Sub Watershed, where 1 outlet observations consist of 2-point sampling. Dedai Sub Watershed has an area about ± 14.454,70 ha located in the subdistrict of West Kalimantan Regency Sintang Dedai. This study consists of two phases: first, field research of Dedai Sub Watershed conducted for 6 days consecutive on 1 outlet observations with a 2-point sampling. Point sampling performed on downstream and upstream Dedai Sub Watershed. Then samples of water counducted analysis of Laboratory Quality and Total Suspended Solid (TSS) health farm Faculty of Agriculture University of Tanjungpura Pontianak. Result of the study showed that the form and pattern of Sub DAS Dedai is a form of bird feathers and dendritic pattern, while the transverse parabolic profile. The order consists of 5 classes, with the value of IKD is 0,0087 km/km2 and belongs to the category of low discharge values of the flow upstreaman average of 0,6787 m3/sec downstream and 4,1976 m3/sec, the correlation coefficient discharge curve (r) of upstream 0,995 and downsream 0,985, with a coefficient of determination (R2) upstream 0,990 and downstream 0,969. Water quality on Sub DAS Dedai has an average pH of upstream 6,78 and downstream 6,46 is still good and the average temperature of the upstream 29,580C and downstream 29,70C still under normal circumstances in nature, whereas the average brightness level of the upstream 1,05 m and downstream 1,13 m. Total Suspended Solid (TSS) values averaged of upstream 5,2 mg/liter and downstream 8,7 mg/liter, while the average value of the upstream sediment discharge of 0,3135 ton/day and downstream 3,2611 ton/day and the correlation coefficient arch sediment (r) of upstream 0,933 and downsream 0,910, with a coefficient of determination (R2) upstream 0,870 and downstream 0,827..